Steady-state analysis of a synchronous reluctance machine using a single coil theoretical basis and finite element techniques - Van der Merwe, Herman (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1993.